Growth and yield of garlic (Allium Sativum L.) influenced by Zn and Fe application - Alam, Shariq Mahmood; Muhammad Arshad Ullah, Imdad Ali Mahmood; Nausherwan N. Nawab, Taj Naseeb; Haider, Syed Ishtiaq; Aamir, Syeda Sana (Food Biology, 2019)
A pot experiment was conducted to investigate the effect of Zn and Fe application on growth and yield of garlic (Allium sativum L.) var. Desi Sufaid at National Agricultural Research Centre, Islamabad during Rabi season 2018-2019. Eight kilogram of sandy clay loam soil was filled in the pots. Four garlic cloves were sown in each pot. The treatments of Zn, Fe and their mixture (1:1 ratio) @ 5 kg ha-1 along with basal dose of N, P and K (100, 75 and 50 mg kg-1) fertilizer were applied at sowing following complete randomized design with three replications. The plants were allowed to stand till maturity and data on growth traits like plant height (cm), pseudo stem diameter (cm), leaf length (cm), leaves plant-1, bulb diameter (cm), cloves (bulb-1), clove weight (g) and bulb yield (g plant-1) were recorded at harvest. The mean data were analyzed statistically. The highest growth attributes like plant height, number of leaves per plant, bulb diameter, cloves, clove weight and bulb yield were harvested with micronutrients (Zn and Fe) along with basal dose of N, P and K (100, 75 and 50 mg kg-1) application which were significantly higher as compared to control. Though, all the treatments showed positive effect through growth characteristics and yield, however, the mixture of Zn and Fe application produced comparable garlic yield among all the treatments which was 6 and 4 (%) higher than that of sole application of Zn and Fe, respectively. Significant improvement in Zn and Fe concentration in garlic plant tissues was observed with the application of Zn and Fe respectively. Overall the combination of both micronutrients performed better than rest of the treatments through improved growth traits and bulb yield.